THE IMPLICATIONS OF IDEATIONAL METAPHORS ON GRAMMATICAL INTRICACY AND LEXICAL DENSITY IN ACADEMIC WRITING: A SYSTEMIC FUNCTIONAL LINGUISTIC APPROACH - Asnita Sirait; Thomson Radesman Lingga; Kristining Seva (PROJECT (Professional Journal of English Education), 2022)
This study aims at investigating the types of ideational metaphor used in scientific texts and analyzing its implications on grammatical intricacy (GI) and lexical density (LD). The data are limited to the scientific articles published on International Journal of Scientific and Technology Research (IJSTR) Volume 10 - Issue 5, May 2021 Edition. This journal aims to promote the theory and practice of sciences, technology, innovation, engineering and management. A qualitative descriptive methodology is applied to this study. In analyzing the data, there are two grand theories used; Halliday’s Systemic Functional Linguistics (1985) to analyze the ideational metaphors and LD & GI formula proposed by Gerot, Linda, and Wignel (1995). An electronic based is also applied to count number of words and clauses containing in the discourse chosen which can be downloaded from http://www.usingenglish.com/resources/. This study found that ideational metaphor impacted on lexical density by showing the dense information conveyed through nominalization and condensed complex clauses. The lexical density found from the data (three representative articles) is  36.75, 49.48 and 40.51. Ideational  metaphor also impacted on the grammatical intricacy shown from the lower rate which is 1.29,1.31, and 1,24. Ideational metaphors characteristic are shown in the nominalization formed from the condensation of subordinate clauses into phrases, the change of process to noun dominated by relational process to goals or agent. This study is expected to be beneficial to lecturers and writers to consider applying ideational metaphors in their academic writing and to English teachers and lecturers to (re)consider the LD and GI of textbooks readibility for students. Keywords:  Ideational Metaphor, SFL, Scientific Text, Lexical Density, Grammatical Intricacy